AN EVALUATION STUDY OF THE RECORDS DISPOSAL PRACTICE FROM 1968-2019 IN THE GENERAL BUREAUOF THE NATIONAL ARCHIVES OF THE REPUBLIC OF INDONESIA - Catur Rahmawati Tejaningrum; Hidayaturahmi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research evaluates the execution of the archival disposal policy from 1968 to 2019 within the General Bureau of ANRI. The study highlights the gap between policy and implementation that caused record accumulation. A qualitative case study methodology was employed, with data gathered through interviews, observations, and document analysis. The results reveal that the disposal activities successfully decreased the archive volume by 63.83%, aligning with the records retention schedule. Nevertheless, efficiency is hindered by insufficient human resources and protracted bureaucratic processes. One participant noted that ‘the implementation was postponed; it was intended for early in the year, but was executed in August, highlighting the issues of time constraints. The policy is deemed suitable but ineffective in practice. Suggested improvements include augmenting human resources, digitizing verification processes, and enhancing standard operating procedures.